Primary leaf‐type ferredoxin 1 participates in photosynthetic electron transport and carbon assimilation in rice. (12th August 2020) - He, Lei; Li, Man; Qiu, Zhennan; Chen, Dongdong; Zhang, Guangheng; Wang, Xiaoqi; Chen, Guang; Hu, Jiang; Gao, Zhenyu; Dong, Guojun; Ren, Deyong; Shen, Lan; et al.
SUMMARY: Ferredoxins (Fds) play a crucial role in photosynthesis by regulating the distribution of electrons to downstream enzymes. Multiple Fd genes have been annotated in the Oryza sativa L. (rice) genome; however, their specific functions are not well understood. Here, we report the functional characterization of rice Fd1 . Sequence alignment, phylogenetic analysis of seven rice Fd proteins and quantitative reverse transcription polymerase chain reaction (qRT‐PCR) analysis showed that rice Fd1 is a primary leaf‐type Fd. Electron transfer assays involving NADP + and cytochrome c indicated that Fd1 can donate electrons from photosystem I (PSI) to ferredoxin‐NADP + reductase. Loss‐of‐function fd1 mutants showed chlorosis and seedling lethality at the three‐leaf stage. The deficiency of Fd1 impaired photosynthetic electron transport, which affected carbon assimilation. Exogenous glucose treatment partially restored the mutant phenotype, suggesting that Fd1 plays an important role in photosynthetic electron transport in rice. In addition, the transcript levels of Fd‐dependent genes were affected in fd1 mutants, and the trend was similar to that observed in fdc2 plants. Together, these results suggest that OsFd1 is the primary Fd in photosynthetic electron transport and carbon assimilation in rice. Significance Statement: Ferredoxins (Fds) play a crucial role in photosynthesis by regulating the distribution of electrons to downstream enzymes; however, the specific functions of multiple Fd genes annotated in the rice genome are not well understood. This study revealed that disruption of rice Fd1, encoding a primary leaf‐type ferredoxin that functions in photosynthetic electron transport, leads to chlorosis and seedling lethality, and that the expression of Fd1 and FdC2 are coordinated in rice.